A Novel Immune-Gene Pair Signature Revealing the Tumor Microenvironment Features and Immunotherapy Prognosis of Muscle-Invasive Bladder Cancer - Zheng, Xiaonan; Zhou, Xianghong; Xu, Hang; Jin, Di; Yang, Lu; Shen, Bairong; Qiu, Shi; Ai, Jianzhong; Wei, Qiang (Frontiers in Genetics, 2021)
Immunotherapy has been a milestone for muscle-invasive bladder cancer (MIBC) but only a small portion of patients can benefit from it. Therefore, it is crucial to develop a robust individualized immune-related signature of MIBC to identify patients potentially benefiting from immunotherapy. The current study identified patients from The Cancer Genome Atlas (TCGA) and immune genes from the ImmPort database, and used improved data analytical methods to build up a 45 immune-related gene pair signature, which could classify patients into high-risk and low-risk groups. The signature was then independently validated by a Gene Expression Omnibus (GEO) dataset and IMvigor210 data. Subsequent analysis confirmed the worse survival outcomes of the high-risk group in both training (P < 0.001) and validation cohorts (P =0.018). Signature-based risk score was proved to be an independent risk factor of overall survival (P < 0.001) and could predict superior clinical net benefit compared to other clinical factors. CIBERSORT algorithm revealed the low-risk group had increased CD8+ T cells plus memory-activated CD4+ T cell infiltration. The low-risk group also had higher expression of PDCD1 (PD-1), CD40 and CD27, and lower expression of CD276 (B7-H3) and PDCD1LG2 (PD-L2). Importantly, IMvigor210 data indicated that the low-risk group had higher percentage of “inflamed” phenotype plus less “desert” phenotype, and the survival outcomes was significantly better for low-risk patients after immunotherapy (P = 0.014). In conclusion, we proposed a novel and promising prognostic immune-related gene pair (IRGP) signature of MIBC, which could provide us a panoramic view of tumor immune microenvironment of MIBC and independently identify MIBC patients who might benefit from immunotherapy.